Effect of Magnetic Treatment of water for irrigation and seed Qualities of the Plant vegetative growth corundum oriandrum sativum of (Baghdad Science Journal, 2011)
Cultured fruits of theCorundum Coriandrum sativum were sown On 11/11 / 2008 in basins containing 15 kg of soil (Silty Loam) .Fruits were divided into two parts the first was soaked in normanl water and the second was magnetized for a period of 24 hours Irrigation was up to (75% of capacity field.Two types of water (normal water and magnetized water)with three repetitions were used the access to magnetic water was supplied from a special electric device. Recorded measurements were plant height the number of stems / plant, weight of plant, number of flowers, 1000 seed weight) during the cultivation period, which ended on 11/5/2009.Results indicated the absence of any effect of magnetic water on plant growth of Fenugreek while seeds treated with a magnetic water showed significantly different characteristics.